The Contagion Effect of the 2007 Global Financial Crisis on the Malaysian Stock Market - Adam, Gawi Mohamed Khalifa (2012)
This paper is an investigation on the impact of the 2007/2008 global financial crisis and foreign exchange rate on the stock market of Malaysia in two sub periods namely, pre-crisis (January 2002 till June 2007) and during crisis (July,2007 till December 2010). The findings showed that the stock market returns in US and Malaysia were depressed during the period of crisis. The correlation coefficient was strongly significant during the period of the crisis. In addition, multiple regression analysis provided evidence that contagion effects exist to the Malaysian stock market did exist during the US financial crisis, however the foreign exchange rate was not significant during the said financial crisis